Pelatihan Post-Produksi (Audio-Visual Editing) Film Indie di Armidale English College Soreang, Bandung - Rangga Saptya Mohamad Permana; Lilis Puspitasari; Sri Seti Indriani (Jurnal Pengabdian Pada Masyarakat, 2019)
INDIE FILM EDITING TRAINING AT ARMIDALE ENGLISH COLLEGE OF SOREANG, BANDUNG REGENCY. A film can be seen as a medium of mass communication because in a film there are elements of entertainment, education, and information. In fact, a film can be an advocacy media that encourages a social change. In the film production management, there are major label and indie label concepts, where the indie label focuses on film content and filmmakers' freedom of expression. The stages that must be passed by a filmmaker in producing a film starts from the stages of development, pre-production, production, post-production, and distribution. The post-production stage is the most important stage that determines whether a film is classified as a quality film or not because it involves the final touch of a film. Therefore, the author decided to make a community service program in the form of post-production indie film training (audio-visual editing) at Armidale English College, Soreang District, Bandung Regency. The purpose of this training is to provide practical understanding and skills in the field of audio-visual editing to the trainees. The various implementation methods used in this training included media communication methods (audio-visual), lecture methods, interactive methods, pre-test and post-test methods, and simulation methods. The results achieved after the training was carried out were that the trainees experienced increased understanding and skills in the context of indie film post-production, especially in the process of audio-visual films editing. Keywords: Audio-Visual, Editing, Indie Film, Post-Production, Training.